Association between Herpes Zoster and Osteoporosis: A Nested Case-Control Study Using a National Sample Cohort. (30th July 2019) - Min, Chanyang; Bang, Woo Jin; Oh, Dong Jun; Sim, Songyong; Choi, Hyo Geun
Abstract : Objectives. Chronic inflammatory disease might affect osteoporosis; however, few studies have reported the association between herpes zoster and osteoporosis. The goal of this study was to estimate the association between herpes zoster and osteoporosis in Korean residents. Methods . The Korean National Health Insurance Service-National Sample Cohort, which includes individuals aged ≥ 50 years, was assessed from 2002 to 2013. In total, 68, 492 osteoporosis participants were matched with 68, 492 control participants at a ratio of 1:1 by age, sex, income, and region of residence. We assayed the prior histories of herpes zoster in the osteoporosis and control groups. The diagnoses of herpes zoster and osteoporosis were based on ICD-10 codes and claim codes. Crude and adjusted models of odds ratios (ORs) were explored using conditional logistic regression analyses, and the 95% confidence intervals (CIs) were computed. The participants were stratified according to age, sex, income, and region of residence. Subgroup analyses were performed to investigate the role of age and sex. Results . The rate of herpes zoster in the osteoporosis group (5.1% [3, 487/68, 492]) was higher than that in the control group (4.0% [2, 738/68, 492]). The adjusted OR of herpes zoster in the osteoporosis group was 1.17 (95% CI = 1.11-1.24). In the subgroup analyses, the adjusted OR was 1.34 (95% CI = 1.01-1.78) among males aged < 65 years, 1.20 (95% CI = 1.12-1.29) among females aged < 65 years, and 1.19 (95% CI = 1.04-1.36) among males aged ≥ 65 years. Conclusion. The ORs of herpes zoster were increased among the osteoporosis patients. This correlation was reliable in all subgroups by age and sex except group of women ≥ 65 years old.